Magnon excitations in vortex-state nanorings - Zaspel, C.E.; Owens, J.W.; Ivanov, B.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The magnon mode excitation spectrum is calculated using the linearized Landau–Lifshitz equations applied to the ring in the vortex ground state. A combination of analytical techniques with numerical evaluation of integrals is used to obtain the mode frequency with the effective magnetostatic volume charge as a small perturbation. In general, the modes can be classified according to radial number n and azimuthal number m. It is shown that the frequency increases as n increases, and the frequency decreases as m increases.